RETRACTED: Analysis of jet currents using the SST turbulence model - Madaliev Murodil; Usmonov Mavlonbek; Ismoilov Muslimbek; Bilolov Inomjon; Israilov Sharobiddin; Abdullajonova Nurzoda; Rajabova Khurshida (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001